The organizational climate and job satisfaction in teachers of a public university (Revista Innova Educación, 2022)
The study determines the relationship between the organizational climate and job satisfaction of teachers at the National University of the Altiplano, Puno (Peru). The deductive method was obtained and the research was of a correlational type, with a non-experimental design and a transactional or transversal type of a single sample cut, whose approach is quantitative. In the methodology, the survey technique was used through the use of a structured questionnaire and for its verification, the statistical tests of Chi square and Spearman's Rho conversion coefficient were used. It will be developed that the organizational climate and job satisfaction will be related in a high positive way, as demonstrated by χ_c^2=26.640, r=0.631. It is concluded that the higher the organizational climate in the teachers of the Universidad Nacional del Altiplano de Puno, the greater personal job satisfaction will be obtained.
Keywords: organizational climate; teachers; job satisfaction; public university